2012
DOI: 10.1597/11-025
|View full text |Cite
|
Sign up to set email alerts
|

Left-Sided Predominance of Hypodontia Irrespective of Cleft Sidedness in a French Population

Abstract: Both right-sided and left-sided clefts were more frequently correlated with left-sided dental agenesis. This left-sided prevalence suggests that common signaling malfunctions might be involved, both in dental development anomalies and cleft genesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
4
20
1
4
Order By: Relevance
“…On the other hand, the prevalence of hypodontia in the permanent dentition of the CL/P subjects was much more frequent (52.7%) in this study, which was similar to rates reported in previous studies: 47.5% (Slayton et al, 2003), 49.8% , 51.1% (Watanabe et al, 2011), and 56.9% (Kadono et al, 2008). The prevalence in this study was relatively lower than that in some previous studies: 63% (Matern et al, 2012), 66.3% (Ohya et al, 1995), 66.7% (Aljamal et al, 2010), 67.6% (Aizenbud et al, 2005), 68.2% (Mori et al, 2005), 77% (Shapira et al, 2000), and 70.2% (Tereza et al, 2010). The finding that the prevalence of hypodontia was lower in primary dentition but higher in permanent dentition was reported in * There was a significant difference in prevalence between the cleft side (C) and the noncleft side (NC).…”
Section: Hypodontiacontrasting
confidence: 82%
“…On the other hand, the prevalence of hypodontia in the permanent dentition of the CL/P subjects was much more frequent (52.7%) in this study, which was similar to rates reported in previous studies: 47.5% (Slayton et al, 2003), 49.8% , 51.1% (Watanabe et al, 2011), and 56.9% (Kadono et al, 2008). The prevalence in this study was relatively lower than that in some previous studies: 63% (Matern et al, 2012), 66.3% (Ohya et al, 1995), 66.7% (Aljamal et al, 2010), 67.6% (Aizenbud et al, 2005), 68.2% (Mori et al, 2005), 77% (Shapira et al, 2000), and 70.2% (Tereza et al, 2010). The finding that the prevalence of hypodontia was lower in primary dentition but higher in permanent dentition was reported in * There was a significant difference in prevalence between the cleft side (C) and the noncleft side (NC).…”
Section: Hypodontiacontrasting
confidence: 82%
“…(7,27,28) A prevalência de agenesia do lado esquerdo é maior do que do lado direito. (13,29) Diversos fatores têm sido sugeridos como colaboradores para a ocorrência da agenesia do incisivo lateral na região das fissuras. A proximidade da fissura, (30) deficiência de aporte sanguíneo congênita ou secundária à cirurgia (31) ou mesmo a deficiência de aporte ectomesenquimal.…”
Section: Agenesia Dentária Em Indivíduos Fissuradosunclassified
“…Dessa maneira o desenvolvimento separado destas estruturas pode originar dois incisivos laterais, um em cada lado da fissura. (38) Enquanto a incidência de agenesia dentária, na maioria dos estudos, aumenta proporcionalmente em relação à extensão da fissura (29,30,31) para os dentes supranumerários esta relação é inversamente proporcional. (23) Associação entre agenesia e dentes surpanumerários em indivíduos com FL/PNS foi demonstrada no estudo de Kuchler et al, (11) entretanto a manifestação conjunta dessas anomalias é rara na população geral.…”
Section: Outras Anomaliasunclassified
“…A prevalência de agenesia no lado esquerdo é significativamente maior do que no direito (Akcam et al 2010, Matern et al 2011. Segundo Matern et al (2011) tanto as fissuras do lado esquerdo como as do lado direito foram relacionadas mais frequentemente à agenesias do lado esquerdo.…”
Section: Agenesia Dentáriaunclassified
“…A incidência de agenesia geralmente aumenta proporcionalmente à extensão da fissura (Kim e Baek 2006, Wu et al 2011, Matern et al 2011. Estudos realizados em indivíduos com fissura labiopalatina bilateral (FLPB) revelaram elevada prevalência de agenesia do incisivo lateral bilateralmente (Vanzin e Yamazaki 2002, Tereza et al 2010.…”
Section: Agenesia Dentáriaunclassified